Diabetic Status of People Affected by Leprosy in Donorojo Leprosy Recovered Village: A Cross Sectional Study - Nadhila Beladina; Asri Adisasmita (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: Just like diabetes, leprosy also cause painless neuropathic ulcers which process is mediated by Schwann-cell. Biochemical changes on leprosy patients presumed to have role on pathogenesis of diabetes mellitus.  Methods: This study is cross-sectional study aimed to know further about diabetic status on population of people affected by leprosy, as the preliminary study to prove the association between diabetes mellitus and leprosy.  Data, such as diabetic status, type of leprosy, grade of disability, and other variables are collected from 127 people affected by leprosy in Donorojo leprosy recovered village.Result: Result showed that 19.7% are having diabetes mellitus, and other 23.6% are in pre-diabetic condition. This number is higher than prevalence of diabetes mellitus in Central Java (2.09%) and Indonesia (2%).Conclusion : Further research is needed to prove the association between leprosy and diabetic status.  All leprosy patients should be recommended to be routinely screened for diabetes mellitus.